Development of a Correlation between the Resilient Modulus and CBR Value for Granular Blends Containing Natural Aggregates and RAP/RCA Materials - Muhammad Arshad (Advances in Materials Science and Engineering)
Limited supplies of natural aggregates for highway construction, in addition to increasing processing costs, time, and environmental concerns, have led to the use of various reclaimed/recycled materials. Reclaimed asphalt pavement (RAP) and recycled concrete aggregate (RCA) have prospective uses in substantial amounts in base and subbase layers of flexible pavement in order to overcome the increasing issue of a shortage of natural aggregates. This research presents the development of an empirical model for the estimation of resilient modulus value (MR) on the basis of CBR values using experimental results obtained for 52 remoulded granular samples containing natural aggregates, RCA, and RAP samples. Statistical analysis of the suggested model shows promising results in terms of its strength and significance when t-test was applied. Additionally, experimental results also show that MR value increases in conjunction with an increase in RAP contents, while the trend for the CBR value is the opposite. Statistical analysis of simulation results using PerRoad and KenPave demonstrates that addition of RAP contents in the subbase layer of flexible pavements significantly improves its performance when considering resistance against rutting and fatigue. However, results of repeated load triaxial tests show that residual accumulative strain under a certain range of loading conditions increases substantially due to the addition of RAP materials, which may be disadvantageous to the serviceable life of the whole pavement structure.